2013
DOI: 10.1063/1.4811760
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic particle-in-cell verification of improving high-power microwave window breakdown thresholds by resonant magnetic field

Abstract: High-power microwave driven vacuum dielectric window breakdown is found to be suppressed by external magnetic field with gyrofrequency Ω = eB/m close to angular frequency ω of rf electric field. This letter gives a particle-in-cell demonstration of the increasing of breakdown thresholds by such magnetic field. It is found that magnetic field with Ω ∼ ω mitigates the multipactor effect. Its saturation process occurs at upper boundary of the susceptibility diagram instead of the lower one. This decreases the dc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Previous study found that vacuum flashover varies with insulator length in form of V flashover = kd α where α is smaller than 1 [34][35][36]. Such conclusion does not contradict with equation (24) if the implicit relation between P crit and d is considered. To determine the critical pressure, one may simplify the gas breakdown and calculate the first Townsend coefficient as a function of pressure and applied electric field.…”
Section: Determination Of Flashover Voltagementioning
confidence: 76%
See 2 more Smart Citations
“…Previous study found that vacuum flashover varies with insulator length in form of V flashover = kd α where α is smaller than 1 [34][35][36]. Such conclusion does not contradict with equation (24) if the implicit relation between P crit and d is considered. To determine the critical pressure, one may simplify the gas breakdown and calculate the first Townsend coefficient as a function of pressure and applied electric field.…”
Section: Determination Of Flashover Voltagementioning
confidence: 76%
“…Theoretical results are compared with our PIC simulation code in figure 3. PIC method is widely used in surface flashover under DC or radio frequency condition [23,24]. Validation of implemented PIC code can be found in our previous studies [22,25,26].…”
Section: Multipactor Expansion and Saturated Stagementioning
confidence: 89%
See 1 more Smart Citation
“…12) The temporal and spatial evolution characteristics of multipactor discharges were extensively investigated by a particle-in-cell method. [13][14][15] The energy of an electron hitting the dielectric surface in a vacuum and at different pressures is obtained by solving the momentum conservation equation of the electron, in order to discuss the effect of desorption gas on dielectric surface discharge. 16) In recent years, some new electron multipactor theories and suppression methods of the multipactor have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The former often occurs on the RF window surface or insulator surface, requires an applied electric field parallel to the dielectric surface and a direct current (DC) electric field from the charging of the dielectric surface, and has been profoundly investigated experimentally, theoretically, and numerically. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The latter requires a resonant RF electric field perpendicular to the plate surface, and often occurs on the waveguide or metal gap. [1,22] Despite the extremely similar physical process, they are always thought to occur on different devices solely and are studied by researchers from different fields separately.…”
Section: Introductionmentioning
confidence: 99%